2004
DOI: 10.1111/j.1467-842x.2004.tb00444.x
|View full text |Cite
|
Sign up to set email alerts
|

Access to infertility investigations and treatment for HIV+ people: a survey of Australian infertility clinics

Abstract: Objective: To examine the availability in Australia of investigations and treatment of infertility for people infected with HIV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…To assess available services, a questionnaire was sent to fertility clinics across Canada (Appendix A). This questionnaire was based on those used in the United Kingdom and Australia studies, as there was no other validated survey instrument available [ 13 , 14 ]. Prior to study initiation, study authors and other physicians reviewed versions of the questionnaire for face validity, and changes were incorporated for content validity and clarity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess available services, a questionnaire was sent to fertility clinics across Canada (Appendix A). This questionnaire was based on those used in the United Kingdom and Australia studies, as there was no other validated survey instrument available [ 13 , 14 ]. Prior to study initiation, study authors and other physicians reviewed versions of the questionnaire for face validity, and changes were incorporated for content validity and clarity.…”
Section: Methodsmentioning
confidence: 99%
“…Barriers to access include not only ethical issues, but also technical difficulties related to the handling of specimens and training of staff. In both the United Kingdom and Australia, studies have been performed to evaluate the accessibility of fertility services for HIV-infected couples [ 13 , 14 ]. The results of these studies were disappointing, with limited access for both investigations and treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Inadequate access to conception planning and assisted reproductive services has been documented in North America, Australia and the United Kingdom, despite the existence of guidelines for reproductive care for PLWHIV (Apoola et al, 2001;Cooper et al, 2009;Frodsham, Boag, Barton, & Gilling-Smith, 2006;Gruskin, Firestone, MacCarthy, & Ferguson, 2008;Minkoff, 2006;Pitts & Shields, 2004;Sauer, 2006;Stanitis, Brow, & Wiczyk, 2008;Yudin, Shapiro, & Loutfy, 2010). Our study showed that although 63% of participants intended a future pregnancy and 44% had a plan for conception in the near future, only 30% had spoken to an HCP about the issue and only 30% had some knowledge about conception planning and assisted reproductive services for safer conception.…”
Section: Discussionmentioning
confidence: 55%
“…International HIV sexual and reproductive health guidelines and pregnancy-planning guidelines under development in Canada are placing increasing importance on comprehensive preconception services as part of receiving good quality of care (World Health Organization [WHO], 2008). At least five European countries have national HIV conception planning programs (Apoola, Tenhof, & Allan, 2001;Bujan et al, 2007;Fakoya et al, 2008;Myer, Morroni, & ElSadr, 2005;Pitts & Shields, 2004;Rozenberg, Gerard, Manigart, Ham, & Delvigne, 2002); however, no such programs exist in Canada. Since there is little existing data regarding the support, services and resources PLWHIV require planning a pregnancy, it is imperative to assess these needs and identify gaps in order to develop programs and resources to support safer and healthier conceptions, pregnancies and future families.…”
Section: Introductionmentioning
confidence: 99%
“…The survey examined the presence of clinic policies regarding provision of services for HIV-infected patients, services provided at the time of the survey, and attitudes toward provision of services for HIV-infected men if the California law were to allow therapeutic use of donated sperm for a designated recipient. The survey was based upon instruments used in previous studies conducted in the United Kingdom and Australia (27,28). We imported all data into a relational database and performed summary statistics using Microsoft Excel 2004 (Microsoft Corp., Redmond, WA).…”
mentioning
confidence: 99%